Retrospective Analysis of Bacterial and Viral Co-Infections in Pneumocystis spp. Positive Lung Samples of Austrian Pigs with Pneumonia - Weissenbacher-Lang, Christiane (PLoS One, 2016)
Aim of this study was the retrospective investigation of viral (porcine circovirus type 2 (PCV2), porcine reproductive and respiratory syndrome virus (PRRSV), torque teno sus virus type 1 and 2 (TTSuV1, TTSuV2)) and bacterial (Bordetella bronchiseptica (B. b.), Mycoplasma hyopneumoniae (M. h.), and Pasteurella multocida (P. m.)) co-infections in 110 Pneumocystis spp. positive lung samples of Austrian pigs with pneumonia. Fifty-one % were positive for PCV2, 7% for PRRSV, 22% for TTSuV1, 48% for TTSuV2, 6% for B. b., 29% for M. h., and 21% for P. m. In 38.2% only viral, in 3.6% only bacterial and in 40.0% both, viral and bacterial pathogens were detected. In 29.1% of the cases a co-infection with 1 pathogen, in 28.2% with 2, in 17.3% with 3, and in 7.3% with 4 different infectious agents were observed. The exposure to Pneumocystis significantly decreased the risk of a co-infection with PRRSV in weaning piglets; all other odds ratios were not significant. Four categories of results were compared: I = P. spp. + only viral co-infectants, II = P. spp. + both viral and bacterial co-infectants, III = P. spp. + only bacterial co-infectants, and IV = P. spp. single infection. The evaluation of all samples and the age class of the weaning piglets resulted in a predomination of the categories I and II. In contrast, the suckling piglets showed more samples of category I and IV. In the group of fattening pigs, category II predominated. Suckling piglets can be infected with P. spp. early in life. With increasing age this single infections can be complicated by co-infections with other respiratory diseases.